Experimental and numerical analysis of granular phase flow behavior in a rotary bed reactor: velocity profile study - Tong, Sirui (2024)
The rotary bed reactor, essentially a rotating drum involving chemical reactions, emerges as a promising option for multiphase reactions due to its effective gas-solid contacts and sustainable input/output of the granular phase. This study integrated the Euler-Euler multiphase model with experiments to examine velocity profiles of the bed layer under varying conditions, including rotating speed, filling level, and material density. Several optimization strategies were proposed for reducing the “dead zone” size under the rolling mode to improve overall heat and mass transfer efficiency. Results validated the model's accuracy and revealed flow behavior characteristics under low rotating speed modes (sliding and slumping). Additionally, increasing rotating speeds, decreasing filling levels, and using higher-density bed materials mitigated the “dead zone” size under the rolling mode. This work advances the understanding of granular hydrodynamic behavior in rotating drums and lays the foundation for the application of such reactors in the field of chemical engineering.